Entwicklung und Stand des Steuerungsverständnisses in der Raumplanung. - Fürst, Dietrich (TH Zürich, ORL-Institut, 2005)
Der Beitrag geht dem Wandel im Steuerungsverständnis der Raumplanung in Deutschland nach. Nach einer kurzen Abklärung des Begriffs der Steuerung in der Raumplanung und der Darstellung der Anfänge der Raum- und Landesplanung in den 1920er und 1930er Jahren wird den späteren Etappen in der Wandlung des Raumplanungs- und Steuerungsbegriffs nachgegangen: von der Planung zur verwaltungsrechtlichen Ordnungspolitik, von der Planungseuphorie in den 1970er Jahren bis zur "bescheidenen" kommunikativen Planung der 1990er Jahre. Als vereinfachende Tendenz kann festgehalten werden, dass die Raumplanung ihren Schwerpunkt immer mehr auf die Regionalplanung verlegt und eine immer ausgefeiltere und diplomatischere Steuerungskunst verlangt. oc/difu

German spatial planning covers nearly 100 years. Planning has always been equated with "steering" and "coordination", but the conception of steering has changed from technocratic to communicative, from plan-making to planning as process, from purely ordering space to developing places, from planning to regional management. "Changed from to" suggests straight lines. In practice, however, we serve extensions and contractions, layers of older and newer concepts, and, most important, the process is not linear but rather shows tips and downs in accordance with the general acceptance of governmental steering, i.e. when state interventions get weaker, spatial-planning loses backing. The explanations for those changes are more closely related to external pressures and internal paradigm changes than to the dynamics of the process itself - with the concept of planning and steering becoming more diversified over time. The present contextual changes (privatization, deregulation, speeding up governmental procedures, etc.) force spatial planning to become more "demand-reactive", which implies the integration of market-based instruments (pricing of scarce natural resources, property rights trading, emission trading, etc.), a more intense collaboration of economic actors, and a closer linking, of spatial planning to spatial development schemes (strategic planning). difu
Keywords: Raumordnung; Raumordnungspolitik; Raumplanung; Planungstheorie; Planung; Geschichte; Ordnungspolitik; Regionalplanung; Governance; Steuerung